Analytical Method for Determining the Viscosity Index of Engine Lubricating Oils - Leszek Chybowski; Marcin Szczepanek; Konrad Ćwirko; Konrad Marosek (Energies, 2024)
This paper proposes a simple analytical method for determining the viscosity index (VI) that effectively aligns with results obtained from the applicable standards. This method simply needs the kinematic viscosity of the tested oil at 40 and 100 °C as input parameters and does not need to use tables that are an integral part of the mentioned standards. This work presents a method and evaluates the accuracy of determining auxiliary parameters in the form of kinematic viscosity values at 40 °C for two hypothetical oils. These oils have a kinematic viscosity at 100 °C equal to that of the oil under testing and have VI = 0 and 100. The relative fitting error percentage and the coefficient of determination are found for the specified auxiliary indicators. The method is validated using data obtained from previous studies in the form of the kinematic viscosity of lubricating oil–diesel mixtures. The mixtures of viscosity grades SAE 30 and SAE 40 lubricating oil with diesel oil at concentrations of 0, 1, 2, 5, 10, 20, and 50% w/w are tested. The viscosity index for each mixture is determined using a standard-based manual calculation using the Anton Paar viscosity index calculator and the proposed method. The results obtained from the proposed analytical method are compared with those from two other methods. The maximum percentage relative fitting error (δmax ≈ 1%) and the coefficient of determination (R2 > 0.999) are determined. The obtained results demonstrate a very good fit and, thus, confirm the usefulness of the proposed approach.